Real-time subsurface scattering with self shadowing using Cg shaders - Martinez, Altair M. (2006)
"The contribution of this thesis is three-fold. Firstly, this thesis presents an image based rendering algorithm for subsurface scattering that runs in in realtime and is implemented on programmable graphics processing hardware using Cg shaders. The algorithm extends the traditonal two-pass shadow mapping algorithm through an improvement on the second pass by incorporating a thickness computation step which computes the thickness at each vertex using the depth values computed in the first pass and uses the thickness value to compute for subsurface scattering using the exponential function to simulate the exponential fall-off light on highly scattering surfaces such as marble. Various results are presented to show the performance of the algorithm as the number of vertices increase and at different dynamic conditions. The algorithm produces softer shadows and lighter complexion in real-time for marble rendered objects. Secondly an approximate model for the Oblation statue of the University of the Philippines is presented and first used in thsi thesis. The Oblation statue model can be used by other researchers in their future studies and for testing their 3D rendering algorithms. This thesis presents in depth theory building on various areas of computer graphics and gives detailed discussion on the implementation of the algorithms. Hence finally, this thesis will serve as a valuable reference for readers and researches who would like to implement their algorithms using programmable vertex and pixel shaders."